Innovation of Moringa Based Food Processing as An Effort to Prevent Stunting: Inovasi Olahan Makanan Berbahan Dasar Kelor Sebagai Upaya Dalam Pencegahan Stunting (JURNAL UNEJ, 2024)
Stunting is a health problem that requires attention. The cause of stunting is chronic malnutrition which results in failure in physical growth and cognitive development in children. Therefore, one of the stunting prevention programs is a nutrition-based approach, especially food innovation that can prevent stunting and utilize the potential of existing resources in society. Moringa is a component that has a lot of potential as a nutritional source to prevent stunting. The aim of this community service is to provide health education through nutrition to prevent stunting. The method involves lectures and discussions about stunting and its prevention, as well as demonstrations of Moringa-based food innovations. This community service was carried out in the Bumi Semeru Damai Agricultural Community, namely pregnant women and mothers with toddlers in Sumbermujur Village, Candipuro District, Lumajang Regency. The results show that there is an increase in respondents' knowledge before and after education. Community service was received very well and warmly by participants. Enthusiastic participants in the event were proven by their activeness in questions and answers. There was an increase in knowledge because the material presented was not only through lectures but also through demonstrations, the material presented was easy to understand and not boring. Respondents felt happy because the friendliness of the education provider, the use of moringa which grows widely in agricultural areas, was a useful part for the respondents. Stunting prevention education by utilizing existing resources around can be used as a step to increase maternal education in increasing awareness and meeting the nutritional needs of stunted children.